Vivaldi antenna based on symmetrical slit lines (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2018)
Introduction. In recent years, the trend has been to use antenna systems whose conductors form a curvilinear slit along the direction of the maximum radiation of the Vivaldi antenna. A rigorous electrodynamic analysis in this case requires large computational costs, so the transition to asymptotic estimates of the radiation field in fixed planes for simpler two-dimensional models allows us to consider the more complex issues of designing slot antennas. Formulation of the problem. As the model for the antenna Vivaldi, we use the mathematical model of the two-sided slit antenna. The antenna model is flat, non-finite, ideally conducting rectangular plate in which there is a thin slit. The field sources and an ideally conducting plate are located at a finite distance from the origin, the field dependence from the distance has the structure of the spherical waves that are removed. Main part. The method is based on the application of the Lorentz lemma to obtain a ratio by calculating the far-field radiation field for a two-way slit antenna located on an ideally conducting plate. In this case, when the variation of the slot antenna is smooth, it was represented in the form of slits of a regular slit line with a constant opening width for a finite number of sections. To do this, we used well-known representations of models that make it possible to calculate the antenna pattern. The relations are applicable to the case of an arbitrary shape of the contour of the plate, arbitrary polarization of the field, and of any size and shape of the gap with a known distribution of the exciting field. Results of the experiment. Theoretical and experimental results obtained during the study of the Vivaldi broadband antenna made in the form of a slit transmission line with an opening width measured exponentially allow us to speak of the correctness of the proposed assumptions. The results of modeling and experimental researches of the antenna testify to the possibility of creating on its base antenna systems that are not inferior in efficiency to volumetric radiators. Using the method of mathematical modeling, samples of the Vivaldi antenna with variable geometric dimensions were calculated and examined. Several variants of the Vivaldi antenna design are considered and their characteristics of the directional pattern in the frequency band 1-18 GHz are examined. Conclusions. The obtained relations are applicable to the case of the arbitrary contour shape of the plate, the arbitrary polarization of the field, and any size and shape of the gap with a known distribution of the excitation field. The given results of simulation and experimental research of antenna testify to the possibility of creating on its basis antenna systems, which are not inferior to the effectiveness of bulk emitters.